2021
DOI: 10.1002/bit.27836
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of perfusion on cardiac microtissue maturation: A heart‐on‐chip platform embedding peristaltic pump capabilities

Abstract: Heart-on-chip is an unprecedented technology for recapitulating key biochemical and biophysical cues in cardiac pathophysiology. Several designs have been proposed to improve its ability to mimic the native tissue and establish it as a reliable research platform. However, despite mimicking one of most vascularized organs, reliable strategies to deliver oxygen and substrates to densely packed constructs of metabolically demanding cells remain unsettled. Herein, we describe a new hearton-chip platform with preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In turn, the NRCM construct viability resulted around 93% ± 2% at day 1 and 88% ± 2.5% at day 7 in µChannels device (Figure 2D(i)), and around 94% ± 1.5% at day 1 and 90% ± 2% at day 7 in the Valve device (Figure 2D(ii)). Such viability data are compatible with previous work on liver [20] and cardiac [21,22,25] cultures within microfluidic devices.…”
Section: Cell Viability and Functionality Assessmentsupporting
confidence: 89%
“…In turn, the NRCM construct viability resulted around 93% ± 2% at day 1 and 88% ± 2.5% at day 7 in µChannels device (Figure 2D(i)), and around 94% ± 1.5% at day 1 and 90% ± 2% at day 7 in the Valve device (Figure 2D(ii)). Such viability data are compatible with previous work on liver [20] and cardiac [21,22,25] cultures within microfluidic devices.…”
Section: Cell Viability and Functionality Assessmentsupporting
confidence: 89%
“…Intermittent cyclic compression yielded to a more aligned cellular morphology, compared to circular cell shape in continuously compressed tissues and better preserved key cardiomyocyte markers (α-actinin and n-cadherin) as compared to non-stimulated constructs. Other recent studies demonstrated the key role of physiological level of flow in improving functional performance and enhancing cellular alignment of both 2D and 3D systems (Cruz-Moreira et al 2021;Kobuszewska et al 2017).…”
Section: Active Stimulationmentioning
confidence: 98%
“…Researchers have developed organ-on-chip models (Fig. 14) for the brain, 208,209 gut, 207,210 heart, 211,212 eyes, 213,214 muscle, 215 lungs, 216,217 liver, 218,219 skin, 220 blood vessels, 221 etc.…”
Section: Organ-on-a-chipmentioning
confidence: 99%